Breaking Bad Habits - Vermeulen, Freek (Ascent Audio, 2020)
Have you ever wondered why most newspapers are so large? Or why management consultants work such long hours? Or why hotels still insist on having check-in desks? Ask anyone in these industries, and their answer will be the same: "That's the way we've always done it." "Best practices" may be widespread, but that doesn't mean they're effective. In many instances the opposite is true: best practices can be outdated, harmful, and a hindrance to innovation. These bad practices are all too common in organizations, and managers and executives can be blind to their pernicious effects. Since they've worked in the past, or have been adopted with success by other firms, their purpose or effectiveness is rarely questioned. As a consequence, these practices spread and persist. In Breaking Bad Habits, Freek Vermeulen, a strategist with a keen eye for the absurd, offers the tools to identify these practices and rid them from your organization. And, most of all, he presents a compelling case for how eliminating popular but outworn ideas, processes, and strategies can create new opportunities for innovation and growth.